Value system of students in Russia and China: the regional dimension (exemplified by Guangzhou and Maikop, Republic of Adygeya) - N P Narbut (RUDN journal of Sociology, 2009)
The article helms the reader to the results of the second stage of the joint Russian-Chinese research project devoted to the comparative analysis of the value system of students in both countries. The comparative analysis of the representative questionnaire survey of Beijing and Moscow students prompted the authors to address the problems of regional differences at home. As a result the researchers turned their attention to value priorities of students of metropolitan and regional institutions of higher education. In Russia the survey was conducted in Maikop (the capital of Adygeya). It has been demonstrated that although value systems of young people in both cities bear enough similarities in their structure and appropriate dominants on the whole, one can observe significant and pronounced differences determined by socio-cultural features of the region as well as by institutional limitations on youth opportunities.